Comparative study of Multiple Criteria Decision Making methods for selecting the best Demand Side Management options - Mokhtar, Muhamad Rasydan; Abdullah, Md Pauzi; Hassan, Mohammad Yusri; Hussin, Faridah (ELEKTRIKA- Journal of Electrical Engineering, 2017)
This paper presents comparative study of multiple criteria decision making (MCDM) methods for analysing Demand Side Management (DSM) options in improving energy efficiency. The solution of selecting the best DSM options contains of weighting the criteria and ranking the options. A method known as Analytical Hierarchy Process (AHP) is used to weighting the criteria. Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE), Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) and Weighted Sum Method (WSM) used to rank the DSM options. Combination of AHP with PROMETHEE (AHP-PROMETHEE), AHP with TOPSIS (AHP-TOPSIS) and AHP with WSM (AHP-WSM) have been applied in a case study where 7 DSM options to be evaluated according to 6 criteria. The results shown 3 sets of ranking order where all approaches shown DSM1 is the most cost effective option while DSM5 is the least cost effective option. However there is slightly different in AHP-TOPSIS ranking order between second priority and third priority while AHP-PROMETHEE and AHP-WSM provide same ranking order. In addition, AHP-WSM and AHP-TOPSIS have an advantage over AHP-PROMETHEE where do not required any pairwise comparison to be completed in ranking process.